Analysis of crack propagation energy and effective unit hindering crack propagation - Aihua Wang; Jing Wang; Yun Peng; Lin Zhao; Yang Cao; Xianglei Kong; Liang Chu; Ziqiang Wang; Guanghui Xu (Journal of Materials Research and Technology)
Impact tests were conducted on deposited metal of 690 MPa HSLA steel with inter-pass temperatures of 80 °C and 200 °C. The micro-structure and crack propagation path in the near fracture zone were observed using OM, SEM, EBSD and other analytical techniques. The study aimed to investigate the crack propagation rules and effective units that hinder crack propagation during the impact process. The results showed that the impact absorption energies were 103.9J and 63.2J, respectively, and the difference in crack initiation and propagation energies were 6 J and 34 J at inter-pass temperatures of 80 °C and 200 °C.The difference in propagation energy is the main reason for the difference in absorption of impact energy. Further research has found that the stable expansion work is 32.1J (80 °C) and 0.4J (200 °C), respectively, with a difference of 31.7J, while the unstable expansion work and tearing expansion work had little difference.The difference in stable expansion work is determined by the different proportions of large angle grain boundaries in the deposited metal. For instance, at 200 °C, the effective unit hindering crack propagation were discussed. The results showed that when the crack propagated through the laths and the lath blocks boundary, there was no turning. However, the propagation direction of the crack changed significantly when it passed through the high angle lath packets boundary. Therefore, it was concluded that the lath packets boundary had a strong blocking effect on the crack propagation, and the laths packets could be used as an effective unit to block crack propagation, with an effective grain size of 5.57 μm(80 °C) and 7.67 μm(200 °C), respectively.